COVID-19 백신 투여 이후 발생한 심한 사지 자반증이 절단을 요하는 당뇨발에 미치는 영향: 증례 보고 - 김병호; 서진수; 장선희; 최준영; Kim, Byung Ho; Suh, Jin Soo; Chang, Sun Hee; Choi, Jun Young (대한족부족관절학회지, 2022)
The current SARS-CoV-2 coronavirus disease 2019 (COVID-19) pandemic has been a particular challenge for diabetes patients. Since these patients are at a higher risk of COVID-19, they have been prioritized for vaccination. In this report, we describe the case of a patient scheduled for diabetic foot amputation who received the first dose of ChAdOx1 nCov-19 vaccine and subsequently developed severe purpura in his genitalia and both of his hands and feet, accompanied by acute renal failure. The operation had to be postponed as severe limb purpura appeared just before the operation. With adequate management for acute renal failure and topical steroid application for the severe purpura lesions, a successful outcome could be obtained after the delayed first ray amputation. We recommend that COVID-19 vaccination should be carefully administered in patients with a diabetic foot requiring amputation.